2021
DOI: 10.1094/pdis-06-20-1312-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Xanthomonas albilineans Causing Leaf Scald on Two Chewing Cane Clones in Zhejiang Province, China

Abstract: In recent years, outbreaks of leaf scald have been reported in two chewing cane clones “Guangdong Huangpi” and “Taoshang Guozhe” in Zhejiang province, China. From May to July 2019, we collected 11 and 13 leaf or stalk samples from symptomatic “Guangdong Huangpi” from four farms in Wenling and “Taoshang Guozhe” clones from three farms in Ruian, Zhejiang province, respectively. Leaves in young plants exhibited white pencil-line streaks (Supplement Fig. 1A & 1D) as well as partial or complete chlorosis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…hybrid), grown within China. However, some Xa strains were collected from a local traditional chewing cane cultivar Taoshangguozhe ( S. officinarum ), collected in the city of Ruian (Zhejiang province), and were proposed to form a new phylogenetic group, Xa-RA, based on MLSA with two ( ABC and gyr B) [ 22 ] or four ( rpo D, gln A, gyr B, and atp D) genes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…hybrid), grown within China. However, some Xa strains were collected from a local traditional chewing cane cultivar Taoshangguozhe ( S. officinarum ), collected in the city of Ruian (Zhejiang province), and were proposed to form a new phylogenetic group, Xa-RA, based on MLSA with two ( ABC and gyr B) [ 22 ] or four ( rpo D, gln A, gyr B, and atp D) genes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strains hosted in the cultivar Taoshangguozhe of S. officinarum formed a separate group, group II, which was distinct from other Chinese strains, whereas the Xa strains hosted in two chewing cane cultivars (Guangdonghuangpi and Badila) of S. officinarum along with Xa strains hosted in modern commercial cultivars clustered into the same group (Group I). Notably, the famous chewing cane cultivar Badila has been cultivated for more than half a century in southern China, while the cultivar Guangdonghuangpi was recently introduced into Zhejiang from Guangdong province [ 22 ]. Almost all Xa strains from China, including those grown in Guangdong province, clustered in the PFGE-B group [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, only X. albilineans strains clustering with foreign strains of PFGE group B were reported in China ( Zhang et al., 2017 ; Ntambo et al., 2019b ). Nevertheless, recent observations suggested that other phylogenetic groups of X. albilineans occur in China ( Duan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%